Model of Increasing Student Understanding Through Strengthening Teacher Professionalism and Classroom Management - Samsul Arifin; Nurdyansyah Nurdyansyah; Benny Prasetiya (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2022)
Increasing students' understanding requires teacher competence in teaching and classroom management preparation. Teacher professionalism has a significant role in increasing student learning motivation, which will impact the achievement of understanding. The purpose of this study is to describe the effect of classroom management and teacher professionalism on students' level of understanding. This study uses a quantitative approach. The research design is descriptive correlational. The subjects in this study were 67 students of Muhammadiyah Plus Probolinggo Elementary School. The data collection technique used in this study was a questionnaire. Data analysis used a path analysis test with the help of SPSS version 24.0. The results of this study namely; 1) Class management is included in the low category, teacher professionalism is high, and the level of student understanding is high; 2) There is no significant influence between classroom management and the level of understanding of students, namely the value of Sig 0.000>0.05; 3) There is a significant influence on teacher professionalism on the level of understanding of students, namely the value of Sig. 0.113>0.05; 4) There is a significant simultaneous influence between classroom management and teacher professionalism on students' level of understanding, namely the value of Sig. 0.104>0.05; Meanwhile, the size of other variables outside the variables studied is 0.797. The implications of this study confirm that teacher professionalism and classroom management positively contribute to increasing student understanding.